THE EFFECTIVENESS OF EXTRACT THE SEED OF POMEGRANATE IN HEALING THE WOUND INDUCED INRABBITS SKIN - Salim, F. D.; Ibrahim, K. M.; Yousif , W. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was conducted to evaluate wound induced in rabbit skin by using alcohols and aqueous extracts of pomegranate seeds. Total flavonoids concentration were estimated using high performance liquid chromatography (HPLC). The highest flavonoids concentration were recorded in ethanol extract. Acute inflammation was induced in laboratory animals (rabbits) by injecting 0.1mL of 2.5% formalin inside the wound incision. Aqueous and ethanol extracts of pomegranate seeds an anti-inflammatory and healing effect compared with the Vaseline on rabbit skin. A histopathological study was conducted to observe healing development of the induced wound which proved that healing of the skin was obvious by vanishing of odema and decrease in scar size, enhancement of fibroblast proliferation, collagen regeneration, Keratinization and Epithelialization. Extracts  have the ability to reduce the inflammation that induced by formalin and appeared to be efficient in healing wounded rabbits skin.